Comparison of interpolation techniques for 3D freehand ultrasound: A phantom experiment - Bermejo, D.; Latorre-Quevedo, P.G.; Zegarra, C.; Alejos, G.P.A.; Romero Gutierrez, S.E.; Castañeda, B.; Alejos, G.P.A. (Institute of Electrical and Electronics Engineers, 2023)
Limited access to advanced medical imaging in rural areas of developing countries due to cost and personnel challenges is addressed through teleultrasound imaging. However, systems like Volume Sweep Imaging (VSI) exhibit spatial limitations, encompassing partially focused regions and poor image quality. This study investigates the potential of 3D freehand reconstruction algorithms using rural teleultrasound equipment. We analyze the integration of 3D reconstruction algorithms and batches to optimize the utility of teleultrasound imaging. Overall, we observe a diversity of behaviors across the interpolation techniques. For instance, the positioning system and time calibration in achieving accurate reconstructions. The results show that the Spherical Kernel interpolation is identified as a high-precision method, much more than VNN. We demonstrate the potential for batches to address the challenges posed by limited resources, paving the way for future work on image-guided surgery.
Keywords: Imaging phantom; Interpolation (computer graphics); Computer science; Kernel (algebra); Computer vision; Artificial intelligence; Calibration; Iterative reconstruction; Medical imaging; Multivariate interpolation; Image (mathematics); Mathematics; Bilinear interpolation; Medicine; Radiology; https://purl.org/pe-repo/ocde/ford#1.02.01